Depolymerization and mineralization rates at 12 Mediterranean sites with varying soil N availability. A test for the Schimel and Bennett model - Delgado-Baquerizo, Manuel; Gallardo, Antonio (Soil Biology and Biochemistry, 2011)
It has been suggested that the relative abundance of soil nitrogen forms should change along an N availability gradient. This model was originally described at a biome scale, and few studies have tested it at other scales. Moreover, none of them has examined whether changes in the relative rates of ammoniﬁcation, nitriﬁcation and depolymerization rates also occurs. Our goal was to test whether these N transformation rates change along an N availability gradient which is likely to exist between forest, shrubs and grasses. We used three N availability indexes (total K2SO4-extractable N, ion exchange membrane N and the sum of N mineralization and depolymerization rates). Depolymerization dominated over mineralization in the two poorest plant communities, while ammoniﬁcation and nitriﬁcation rates dominated in intermediate and nutrient rich plant communities respectively. These results conﬁrm that the Schimel and Bennett model can be applied at a regional scale, and that N availability may be modulating not only the dominant N form, but also the relative abundance of a particular N transformation rate.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Ammoniﬁcation rate; Nitriﬁcation rate; nitrogen cycle; soil ammonium; Soil DON; Soil nitrate